2020
DOI: 10.1007/s00203-020-02058-9
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing-based analysis of the composition and diversity of endophytic bacterial community in seeds of upland rice

Abstract: Upland rice is an ecotype crop formed by long-term domestication and evolution of rice in the dry land without water layer. Generally, its stem and leaf are thick and luxuriant, its leaf is wide and light, its root system is developed, its root hair is abundant, its osmotic pressure of root and cell juice concentration of leaf are high, and it is drought resistant, heat-resistant and water absorbing. The purpose of this study is to reveal the "core flora" of endophytes in upland rice seeds by studying the dive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 78 publications
2
15
0
Order By: Relevance
“…A large number of studies on the community structure and diversity of endophytic bacteria in plant seeds have also found that although there are coexisting endophytic dominant bacterial groups among different varieties of plant seeds, at the same time, they have signi cant differences in endophytic bacterial community structure and diversity (Xu et 2019). Although some studies have found that the endophytic bacterial community structure and diversity among different varieties of seeds are very similar, there are still some differences in the abundance of bacterial groups (Zhang et al 2018b;Wang et al 2020). However, there are no signi cant differences in endophytic bacterial diversity and community structure in some upland rice seeds, and they are particularly close in PCoA and NMDS results (Fig.…”
Section: Analysis Of Environmental Factors Affecting the Community St...mentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of studies on the community structure and diversity of endophytic bacteria in plant seeds have also found that although there are coexisting endophytic dominant bacterial groups among different varieties of plant seeds, at the same time, they have signi cant differences in endophytic bacterial community structure and diversity (Xu et 2019). Although some studies have found that the endophytic bacterial community structure and diversity among different varieties of seeds are very similar, there are still some differences in the abundance of bacterial groups (Zhang et al 2018b;Wang et al 2020). However, there are no signi cant differences in endophytic bacterial diversity and community structure in some upland rice seeds, and they are particularly close in PCoA and NMDS results (Fig.…”
Section: Analysis Of Environmental Factors Affecting the Community St...mentioning
confidence: 99%
“…Studies on the root microbial diversity of upland rice and its effects on the growth and drought tolerance of upland rice have also been reported (Pang et al 2020). Our research group also explored the diversity and community structure of endophytic bacteria in upland rice seeds in different regions of China and preliminarily revealed the core microbiota of endophytic bacteria in upland rice seeds (Wang et al 2020).…”
Section: Analysis Of Environmental Factors Affecting the Community St...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a better starting point to obtain plant microbes would be to focus on the study of the seed endomicrobiota (Matsumoto et al, 2021;Moreira et al, 2021); this especially since they are selected generation to generation for the ability to enter the host plant (Hardoim et al, 2008). Nevertheless, seeds have already shown to be a microbiota reservoir providing beneficial traits to the host plant (Ewald, 1987;Rudgers et al, 2009;Hardoim, 2019;Wang et al, 2021). Jasione persistent OTUs were genera Pseudomonas spp., Ralstonia spp., Undibacterium spp., Cutibacterium spp., and Kocuria spp.…”
Section: Core Bacterial Endophytes Of Jasionementioning
confidence: 99%
“…are common plant endophytes (Compant et al, 2011;Pacifico et al, 2019;Wang et al, 2021), acting also as biocontrol agents (Munakata et al, 2020) and members of the core microbiome of many plant species, including canola (Brassica napus) (Moreira et al, 2021). Recently, Pseudomonas has been found in rice plants with the ability to decrease arsenic translocation from roots into grains (Dolphen and Thiravetyan, 2019;Wang et al, 2021), and in lettuce roots as rare microbiota that protect against plant pathogens (Cardinale et al, 2015). Accordingly, other PGPB species, including Cutibacterium spp., identified in wheat (Triticum) seeds (Kuźniar et al, 2020;Abdullaeva et al, 2020); Undibacteriumin spp.…”
Section: Core Bacterial Endophytes Of Jasionementioning
confidence: 99%